Effect of silver particle-longkong peel extract coating on postharvest decay and browning in longkong fruit - Lichanporn, Intira; Techavuthiporn, Chairat; Wongs-Aree, Chalermchai (My University, 2020)
We aimed to assess the effect of longkong peel extract (LPE)-silver particle-alginate coating on the postharvest decay and browning of longkong fruit during storage at 13°C and 90–95% relative humidity (RH). Longkong was coated with 0, 0.45 or 0.90 mg·L−1 LPE in silver particle-alginate solution and then stored at 13°C and 90–95% RH for nine days. In the mixture consisting of the longkong peel extract and silver solution, the silver particle size was modified to yield fine particles. Electron micrography showed the presence of silver particle sizes ranging in size from approximately 71–625 nm. Fruit coated without LPE exhibited severe browning, weight loss and decay incidence during storage. Coating with 0.45 and 0.90 mg·L−1 LPE significantly inhibited the increase in fruit browning by mainly reducing peroxidase (POD) and polyphenol oxidase (PPO) activities. LPE coating effectively reduced the longkong weight loss and decay incidence. No fruit treatment showed a significant titratable acidity change or increased soluble solids at the end of storage. These results indicate that coating with LPE is a promising approach to inhibit decay and browning and to maintain the quality of longkong during low-temperature storage.
Keywords: Coating; Longkong peel extract; Polyphenol oxidase; Silver particles